Do Reading Difficulty Factors Affect TOEFL Reading Scores?: A Study of Non-English Major Students - Rahmani, Eka Fajar; Fauzi, Chandra (FKIP Universitas Lampung, 2025)
Reading comprehension is quite important for non-English major students—especially in academic settings where access to English-language resources is required. Objective: The purpose of this study is to investigate among 143 non-English major students at Universitas Tanjungpura the relationship between the observed reading comprehension difficulties and TOEFL reading performance. Method: Using a descriptive correlational design, data were collected through a 25-item Likert-scale questionnaire measuring five key variables: vocabulary knowledge, grammatical complexity, prior knowledge, test anxiety, and time constraint. TOEFL reading scores were obtained from Educational Testing Service (ETS) practice tests. Findings: Pearson correlation analysis revealed a modest but statistically significant positive correlation between perceived difficulty factors and TOEFL reading scores (r = 0.3497, p < .01). Among the variables, vocabulary knowledge (r = 0.428, p < .01) and grammatical complexity (r = 0.397, p < .01) showed the strongest relationships with performance. Multiple regression analysis confirmed that all five factors accounted for 23.2% of the variance in TOEFL reading scores (F(5,137) = 9.314, p < .001), with vocabulary knowledge (β = .259, p < .01) and grammatical complexity (β = .220, p < .05) emerging as the most significant predictors. These results demonstrate how important it is to include psychological and language elements into reading instructions. This study offers a novel addition by linking students' perceived reading difficulties with actual exam performance in the understudied setting of Indonesian non-English majors. Conclusion: This study emphasizes also the importance of customized teaching strategies addressing particular challenges experienced by these students. Teachers or lecturers, in this situation, can better help non-English majors in raising their reading competence and general academic achievement by concentrating on strengthening vocabulary and grammatical knowledge. Future studies urged to investigate other elements including reading techniques and student motivation. Keywords: correlational study, non-English major students, perceived difficulties, reading comprehension, TOEFL.